The importance of measuring system analysis in process - Ranisavljev, Miloš; Štrbac, Branko; Lanc, Zorana; Matin, Ivan; Hadžistević, Miodrag; Janković, Predrag (Journal of Production Engineering, 2023)
The implementation of statistical methods in the product development phases has become an unavoidable part of engineering practice. Monitoring of the condition of the process or production equipment is performed using established methodologies, which include the analysis of process capabilities. This analysis involves identifying the need to evaluate the production process or system, data collection, analysis, and interpretation of data. Data acquisition is performed using a measuring system, which with its characteristics in terms of accuracy and precision must meet certain criteria. This paper aims to determine the capability of the process, calculating the capability indices Cp and Cpk, with special reference to the measurement system. Before using the data in the analysis of abilities, an analysis of the measurement system was previously performed to determine its variation in the total variation of the study. The variation of the measuring system proved to be acceptable, which gave the author a sufficient reason to further exploit that measuring system. The process capability study was conducted on a sample of 125 parts, where it was concluded that the observed process is within the statistical control limits and can produce most of the workpieces within the specification limits.